2012
DOI: 10.1161/strokeaha.112.669465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Focal Ischemia on Long Noncoding RNAs

Abstract: Background and Purpose Long noncoding RNAs (lncRNAs) play a significant role in cellular physiology. We evaluated the effect of focal ischemia on the expression of 8,314 lncRNAs in rat cerebral cortex using microarrays. Methods Ischemia was induced by transient middle cerebral artery occlusion. Genomic and transcriptomic correlates of the stroke-responsive lncRNAs and the transcription factor binding sties in their promoters were evaluated with bioinformatics. Results 359 lncRNAs were upregulated (>2-fold)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
134
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 13 publications
3
134
0
1
Order By: Relevance
“…They were significantly correlated with non-coding RNAs [18]. Moreover, in the rat cerebral cortex, the promoters of stroke-responsive long non-coding genes and their homologous protein-coding genes showed highly overlapping transcription factor binding sites [36]. These two researches supported the possible sharing of common transcription factors between proteincoding and non-coding genes.…”
Section: Lncrnas May Share Common Transcription Factors With Protein mentioning
confidence: 68%
“…They were significantly correlated with non-coding RNAs [18]. Moreover, in the rat cerebral cortex, the promoters of stroke-responsive long non-coding genes and their homologous protein-coding genes showed highly overlapping transcription factor binding sites [36]. These two researches supported the possible sharing of common transcription factors between proteincoding and non-coding genes.…”
Section: Lncrnas May Share Common Transcription Factors With Protein mentioning
confidence: 68%
“…LncRNA profiles have been identified through microarray and high-throughput sequencing analyses to determine the regulatory function of lncRNAs in diseases. Dharap performed microarray analysis of rat cerebral cortex and revealed that lncRNA expression profiles are significantly altered after stroke [7]. Wu [8] and Dharap [9] performed microarray analysis of rat brain tissues to identify and explore the potential function of lncRNA-N1LR.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the overexpression of the RERT lncRNA upregulated EGLN2 (34). Dharap et al found 62 stroke-responsive lncRNAs showing 90% sequence homology with exons of protein-coding genes in their study on lncRNA expression profiles in focal ischemia (35). Similarly, Ziats et al reported that most differentially expressed lncRNAs in autism spectrum disorders (ASD) were from intergenic regions (~60%), from antisense to proteincoding loci (~15%), or within introns of protein-coding genes (~10%), with the others representing overlapping transcripts from exons or introns in both sense and antisense directions (36).…”
mentioning
confidence: 99%